Improvement of DNA recognition through molecular imprinting: hybrid oligomer imprinted polymeric nanoparticles (oligoMIP NPs). (28th October 2015) - Brahmbhatt, H.; Poma, A.; Pendergraff, H. M.; Watts, J. K.; Turner, N. W.
Abstract : Here we describe the production and characterization of oligoMIP NPs in which we have preorganized the oligonucleotide binding by molecular imprinting technology. Abstract : High affinity and specific binding are cardinal properties of nucleic acids in relation to their biological function and their role in biotechnology. To this end, structural preorganization of oligonucleotides can significantly improve their binding performance, and numerous examples of this can be found in Nature as well as in artificial systems. Here we describe the production and characterization of hybrid DNA–polymer nanoparticles (oligoMIP NPs) as a system in which we have preorganized the oligonucleotide binding by molecular imprinting technology. Molecularly imprinted polymers (MIPs) are cost-effective "smart" polymeric materials capable of antibody-like detection, but characterized by superior robustness and the ability to work in extreme environmental conditions. Especially in the nanoparticle format, MIPs are dubbed as one of the most suitable alternatives to biological antibodies due to their selective molecular recognition properties, improved binding kinetics as well as size and dispersibility. Nonetheless, there have been very few attempts at DNA imprinting in the past due to structural complexity associated with these templates. By introducing modified thymine bases into the oligonucleotide sequences, which allow establishing covalent bonds between the DNA and the polymer, we demonstrate that such hybrid oligoMIP NPs specifically recognize their target DNA, and that the unique strategy of incorporating the complementary DNA strands as "preorganized selective monomers" improves the recognition properties without affecting the NPs physical properties such as size, shape or dispersibility.